Professional learning networks : facilitating transformation in diverse contexts with equity-seeking communities - Schnellert, Leyton (Bingley, U.K. : Emerald Publishing Limited, 2020)
In a time of rapid policy and curriculum change, educators must be knowledge workers who continue to develop professionally. This book offers a critical exploration of how Professional Learning Networks (PLNs) equip educators to work collaboratively to develop their professional practice and be agents of innovation in their field. Providing access to six real-life examples of equity-oriented Professional Learning Networks, this book illustrates key attributes that build educators' practice, expertise, and investment in innovation. Crucially, the authors shine a light on the ability of PLNs to address questions of equity, both for educators working in remote and rural communities who have limited access to professional development and other resources, and diverse learners from equity-seeking communities. This book is of interest to readers from scholarly, practitioner, and policy backgrounds who want to gain an innovative look at real-life cases to inform current and future equity-oriented PLNs. Readers will discover the importance and potential of centering teachers, students, inquiry, collaboration, and context within educational transformation efforts.
Chapter 1. Exploring the potential of professional learning networks / Leyton Schnellert -- Chapter 2. Collaborative professionalism across cultures and contexts / Shanee A. Washington & Michael T. O'Connor -- Chapter 3. Professional learning networks among district leaders / Catherine McGregor, Judy Halbert & Linda Kaser -- Chapter 4. Tracing cycles of teachers' self- and co-regulated practice within a professional learning network / Deborah L. Butler, Leyton Schnellert -- Chapter 5. How rural educators improve professional capital in a blended professional learning network / Min Jung Kim & Karen Martin -- Chapter 6. Growing the top / Trista Hollweck -- Chapter 7. Shifting our gaze / Joelle Rodway & Elizabeth Farley-Ripple.
Includes index.
Includes bibliographical references.
Print version record.
Keywords: Professional learning communities; Employees -- Coaching of; Teachers -- Training of; Education -- Training & Certification; Teaching skills & techniques